(untitled) (Journal of Scientific Research, 2012)
Synthesis and characterization of Ag/PVA nanocomposite and comparison of its anti-bacterial activity with bacteriocin (nisin) for some pathogenic bacteria was carried out. Applications of the bacteriocin include dental care products, pharmaceutical products such as stomach ulcers, colon infection treatment and potential birth control. Ag/PVA nanocomposite was prepared by in situ reduction method, in which silver nitrate, gamma irradiation and poly(vinyl alcohol) (PVA) act as precursor, reductant and stabilizer, respectively. The synthesized Ag nanoparticles (Ag-Nps) have potential antibacterial activity toward both Gram-positive and Gram-negative bacteria. Further studies by X-ray diffraction (XRD) and transmission electron microscopy (TEM) have demonstrated the structure and the distribution of Ag nanoparticles caped within PVA polymer chain. © 2013 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. doi: http://dx.doi.org/10.3329/jsr.v5i1.11828 J. Sci. Res. 5 (1), 151-160 (2013)